Intermolecular Potential - Singh, Kartar (Defence Science Journal, 2014)
Intermolecular potential plays a dominant role in determining the properties of gases, liquids and solids. The equilibrium and transport properties are dependent upon both attractive and repulsive terms in the potential. The scattering cross sections are determined mainly by the repulsive term. Both theoretical and experimental investigations for determining intermolecular potential between helium atoms are fairly extensive. Recent quantum mechanical calculations of interaction energy between two ground state helium atoms are reviewed.